Biomass Utilisation Strategies for Applications in Novel Polymer and Polymer Resin Production. Issue 1 (February 2017) - Kosalka, Justin J.S.; Sacripante, Guerino G.; Lough, Alan J.; Foucher, Daniel A.; Gossage, Robert A.
The synthesis and full characterisation, including in one case via single crystal X-ray diffraction, of two novel bio-derived aromatic monomers are reported. These materials, incorporating a Eugenol or Vanillin molecular skeleton are modified to incorporate diol chains obtained from reaction with glycerine carbonate. They are further characterised by the presence of other groups (e.g., allyl) which are also capable of engendering polymerisation. Facile heat induced self-polymerization is noted in one of the new monomers. The compounds are further tested in block co-polymer synthesis and found to form blocks with simple co-monomers such as succinic acid.